Growth of Tl(2)Ba(2)CaCu(2)O(7) Thin Films on Curved Substrates for Metamaterial Applications - Speller, S; Hao, T; Stevens, C; Edwards, D; Grovenor, C (2008)
Recent developments in the field of magnetic metamaterials have shown that coupled split-ring resonator (SRR) structures can manipulate magnetic fields on a scale shorter than the wavelength of the electromagnetic radiation [1]. In particular, stacks of copper/dielectic SRR structures can be used as high Q filters or as waveguides in near field imaging applications [2]. However, major improvements in the sensitivity of such devices would be achieved by fabricating the SRR elements from high temperature superconducting (HTS) films on appropriate dielectric substrates. In order to produce a stack of superconducting/dielectric SRR structures, the ideal method involves patterning them into an HTS film grown on the curved surface of a dielectric cylinder. To our knowledge this has not previously been attempted on the small scale required for these applications. The desired feature sizes range from a few millimetres for filter applications down to about 10μm for high resolution imaging applications. We report here our initial attempts at the growth of Tl 2Ba2CaCu2O7 (Tl-2212) thin films on the surface of LaAlO3 and MgO single crystal cylinders of diameter 3mm and length 5mm. Scanning Electron Microscopy, Electron Backscatter Diffraction and a novel X-ray Diffraction technique have been used to study the microstructure and analyse the growth morphology of the Tl-2212 films in this unusual geometry. Simulations have been carried out on an axial array of SRR structures that could be fabricated from these HTS/dielectric cylinders. © 2008 IOP Publishing Ltd.